Hantzsch ester as hole relay significantly enhanced photocatalytic hydrogen production. Issue 23 (7th November 2018) - Ma, Liu-Bo; Liu, Ya-Nan; Liang, Kuang; Fang, Xiao-Xiang; Sahar, Shafaq; Kombo, Miza; Xu, An-Wu
Abstract : Hantzsch ester (DHPE) retards the recombination of electron–hole pairs through extracting holes from g-C3 N4, thus dramatically improving visible photocatalytic hydrogen production. Abstract : Polymeric graphitic carbon nitride (g-C3 N4 ) has emerged as a promising semiconductor photocatalytic material, which can convert solar energy into chemical energy under visible-light irradiation. However, because of the issue of recombination of photogenerated electron–hole pairs, the photocatalytic efficiency of g-C3 N4 is dissatisfactory. Herein, we constructed a novel system of graphitic-C3 N4 composite photocatalyst (C3 N4 /DHPE) through π–π interactions and hydrogen bonds for efficient visible light-driven H2 evolution. The Hantzsch ester (diethyl 1, 4-dihydro-2, 6-3, 5-pyridine dicarboxylate, denoted as DHPE) not only speeds up the transfer rate of photogenerated charge carriers, but also retards the recombination of electron–hole pairs through extracting holes from g-C3 N4 . C3 N4 /DHPE hybrid photocatalyst exhibits efficient spatial separation of photogenerated electrons and holes and thus, more electrons can be released for hydrogen production. When 4% DHPE was introduced, the hydrogen production rate of C3 N4 /DHPE photocatalyst drastically increased up to 1345.0 μmol h −1 g −1, which is 4.7 times higher than that of pure g-C3 N4 (286.0 μmol h −1 g −1 ). Moreover, there is no significant decrease in H2 production after a long time reaction (20 h, five test cycles), confirming that the C3 N4 /DHPE photocatalyst has excellent stability. Our study offers a simple, cost-effective, and powerful route to promoting efficient separation of photogenerated charge carriers and a novel strategy to design other highly efficient photocatalytic systems for solar energy conversion.